Negative pole piece, preparation method thereof and battery
By introducing a second negative electrode coating of layered multi-metal oxide into the negative electrode sheet of the sodium ion battery, the problem of insufficient ion diffusion rate and sodium ion transmission speed of the negative electrode sheet in the prior art is solved, and better cycling stability and fast charging performance are achieved.
Patent Information
- Application Number
- CN202411514900.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-10-29
AI Technical Summary
The existing negative electrode sheets of sodium ion battery have shortcomings in ion diffusion rate and sodium ion transfer rate, resulting in poor cycle stability and fast charging performance.
A negative electrode sheet is used, which includes a current collector, a first negative electrode coating and a second negative electrode coating. The second negative electrode coating contains layered multi-metal oxides, which have specific capacity, specific surface area, porous structure and layer spacing characteristics to improve the ion diffusion rate and the transfer rate of sodium ions.
By increasing the ion diffusion rate of the negative electrode sheet and the transmission speed of sodium ions, the cycle stability and fast charging performance of the battery are significantly improved, and the service life of the battery is extended.
Smart Images

Figure BDA0005106573630000201 
Figure BDA0005106573630000211 
Figure BDA0005106573630000221
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode sheet and a preparation method thereof, and a battery. Background Art
[0002] As market demand increases, the development of lithium-ion batteries may be constrained by lithium resources. Lithium accounts for only 0.0065% of the earth's crust, and lithium resources are not abundant and are unevenly distributed geographically. It is foreseeable that the application of lithium-ion batteries will be severely restricted by lithium resources in a few decades.
[0003] Sodium-ion batteries are another type of energy storage battery with a similar working mechanism and battery structure to lithium-ion batteries. Sodium-ion batteries have received increasing attention recently. The abundance of sodium resources is much higher than that of lithium, and they are evenly distributed around the world. They are cheap and stable, and there is no development bottleneck. Since sodium is easily available and cheap, and the negative current collector of sodium batteries can use aluminum foil instead of copper foil like lithium batteries, sodium-ion batteries have great potential price advantages. The material cost of sodium-ion batteries has room to drop by 30% to 40% compared to lithium-ion batteries. With the continuous deepening of research, the potential advantages of sodium-ion batteries are constantly being explored, especially the excellent performance at high and low temperatures and high safety, which lays a good foundation for the application of sodium-ion batteries in the fields of energy storage and power.
[0004] In the related art, the negative electrode plates of sodium ion batteries mostly include a current collector and a negative electrode active material layer (also called a negative electrode coating) disposed on the current collector. However, the structure or composition of the existing negative electrode plates still have more or less deficiencies. For example, the ion diffusion rate or the sodium ion transmission speed in the negative electrode plates needs to be improved, so that the cycle stability and fast charging performance of the battery using the negative electrode plates need to be further improved.
[0005] Therefore, it is urgent to develop a new type of sodium-ion battery negative electrode plate to improve the cycle performance and fast charging performance of sodium-ion batteries. Summary of the invention
[0006] In view of this, the present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the present invention provides a negative electrode plate and a preparation method thereof and a battery, which can improve the ion diffusion rate, facilitate the rapid transmission of sodium ions on the surface of the negative electrode plate, and further facilitate the improvement of the cycle stability and fast charging performance of the battery using the negative electrode plate.
[0007] In order to solve the above technical problems, this application is implemented as follows:
[0008] According to one aspect of the present application, an embodiment of the present application provides a negative electrode plate, the negative electrode plate comprising:
[0009] current collector;
[0010] A first negative electrode coating is disposed on at least one side of the current collector along the thickness direction, wherein the first negative electrode coating comprises a negative electrode active material; and
[0011] The second negative electrode coating is disposed on a surface of the first negative electrode coating away from the current collector, wherein the second negative electrode coating comprises a layered multinary metal oxide, wherein the layered multinary metal oxide comprises at least two metal elements, and the layered multinary metal oxide satisfies at least one of the following characteristics:
[0012] (I) The capacity of the layered multi-metal oxide is ≥ 100 mAh / g;
[0013] (II) The specific surface area of the layered multi-metal oxide is ≥ 100 m 2 / g;
[0014] (III) the layered multi-metal oxide has a porous structure;
[0015] (IV) The interlayer distance of the layered multi-metal oxide is ≥0.15 nm.
[0016] In some embodiments, the capacity of the layered multi-metal oxide is 100 to 800 mAh / g, preferably 100 to 750 mAh / g.
[0017] In some embodiments, the specific surface area of the layered multi-metal oxide is 100 to 200 m 2 / g, preferably 120 to 170 m 2 / g.
[0018] In some embodiments, the pore size of the porous structure ranges from 10 nm to 20 nm, preferably from 14 nm to 16 nm.
[0019] In some embodiments, the interlayer distance of the layered multi-metal oxide is 0.2 nm to 1.0 nm, preferably 0.3 nm to 0.8 nm.
[0020] In some embodiments, the layered multi-metal oxide has a general chemical formula of M1 2+ x M2 3+ y O z , wherein M1 and M2 are selected from transition metal elements respectively, wherein 0.4≤x≤0.8, 0.2≤y≤0.4, and z=(2x+3y) / 2.
[0021] In some embodiments, the M1 includes at least one of Ni, Zn, Mn, Mg, Cu or Co, the M2 includes at least one of Fe, Bi, Al, V or Co, and M1 and M2 are not selected from Co at the same time.
[0022] In some embodiments, the negative electrode active material includes at least one of graphite, soft carbon or hard carbon.
[0023] In some embodiments, the first negative electrode coating further includes a first binder and a first conductive agent.
[0024] In some embodiments, the first binder includes at least one of polyvinylidene fluoride, styrene-butadiene rubber, sodium hydroxymethyl cellulose, polyacrylic acid, polyacrylate, polyvinyl alcohol, polytetrafluoroethylene, polyethylene oxide, carboxypropyl methyl cellulose or hexafluoropropylene.
[0025] In some embodiments, the first conductive agent includes at least one of conductive carbon black, conductive graphite, carbon nanotubes, graphene, or vapor-grown carbon fibers.
[0026] In some embodiments, the mass ratio of the negative electrode active material, the first conductive agent and the first binder is (90-94): (1-6): (2-4).
[0027] In some embodiments, the second negative electrode coating further includes a second binder and a second conductive agent.
[0028] In some embodiments, the second binder includes at least one of polyvinylidene fluoride, styrene-butadiene rubber, sodium hydroxymethyl cellulose, polyacrylic acid, polyacrylate, polyvinyl alcohol, polytetrafluoroethylene, polyethylene oxide, carboxypropyl methyl cellulose or hexafluoropropylene.
[0029] In some embodiments, the second conductive agent includes at least one of conductive carbon black, conductive graphite, carbon nanotubes, graphene, or vapor-grown carbon fibers.
[0030] In some of the embodiments, the mass ratio of the layered multi-metal oxide, the second conductive agent, and the second binder is (90-94): (2-6): (2-4).
[0031] In some embodiments, the second negative electrode coating has a thickness of 2 μm to 6 μm.
[0032] In some embodiments, a thickness ratio of the second negative electrode coating to the first negative electrode coating is 1:(10-30).
[0033] According to another aspect of the present application, an embodiment of the present application provides a method for preparing a negative electrode sheet, which comprises the following steps:
[0034] Coating a first negative electrode slurry on at least one side of the current collector to obtain a first negative electrode coating;
[0035] Coating a second negative electrode slurry on the surface of the first negative electrode coating to obtain a second negative electrode coating;
[0036] The first negative electrode coating layer includes a negative electrode active material, and the second negative electrode coating layer includes a layered multi-metal oxide.
[0037] In some embodiments, the preparation of the layered multi-metal oxide includes: mixing M1 salt, M2 salt, water and urea, and subjecting the mixture to hydrothermal reaction, washing, drying, calcining and ball milling to obtain the layered multi-metal oxide.
[0038] In some embodiments, the anions of the M1 salt and the M2 salt respectively include at least one of nitrate ion, sulfate ion, chloride ion or acetate ion.
[0039] In some embodiments, the M1 element of the M1 salt includes at least one of Ni, Zn, Mn, Mg, Cu or Co, and the M2 element of the M2 salt includes at least one of Fe, Bi, Al or V.
[0040] In some embodiments, the molar ratio of the M1 salt, the M2 salt and the urea is (5-7):(0.5-1.5):10.
[0041] In some embodiments, the temperature of the hydrothermal reaction is 120° C. to 180° C., and the time of the hydrothermal reaction is 8 h to 12 h.
[0042] In some embodiments, the calcination temperature is 450° C. to 500° C., and the calcination time is 1 h to 2 h.
[0043] In some embodiments, the ball milling speed is 50 to 70 r / min, and the ball milling time is 12 h to 24 h.
[0044] In some embodiments, the preparation of the first negative electrode slurry includes: uniformly mixing the negative electrode active material, the first conductive agent and the first binder in a solvent to obtain the first negative electrode slurry;
[0045] The preparation of the second negative electrode slurry includes: uniformly mixing the layered multi-metal oxide, the second conductive agent and the second binder in a solvent to obtain the second negative electrode slurry.
[0046] In some of these embodiments, the first negative electrode slurry is coated on the surface of the current collector, and after drying, a first negative electrode coating is formed on the surface of the current collector; the second negative electrode slurry is coated on the first negative electrode coating, and after drying, a second negative electrode coating is formed on the surface of the first negative electrode coating to obtain a negative electrode sheet.
[0047] According to another aspect of the present application, an embodiment of the present application provides a battery, which includes a positive electrode sheet and a negative electrode sheet, and the negative electrode sheet is the aforementioned negative electrode sheet or a negative electrode sheet prepared according to the aforementioned method.
[0048] In some of these embodiments, the positive electrode sheet includes a positive electrode coating, the positive electrode coating includes a positive electrode active material, and the positive electrode active material includes a Prussian blue-based positive electrode material.
[0049] In some of these embodiments, the chemical general formula of the Prussian blue-based positive electrode material is Na x M3[M4(CN)6] y ·zH2O, 0 < x ≤ 2, 0.8 ≤ y ≤ 1, 0 < z ≤ 20, and M3 and M4 are respectively selected from transition metal elements.
[0050] In some of these embodiments, the positive electrode coating further includes a positive electrode conductive agent and a positive electrode binder, and the mass ratio of the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder is (90-94):(1-6):(2-4).
[0051] Implementing the technical solution of the present invention has at least the following beneficial effects:
[0052] In the embodiment of the present application, for the provided negative electrode sheet, a first negative electrode coating and a second negative electrode coating are sequentially arranged on the surface of the current collector. Among them, the layered multi-metal oxide in the second negative electrode coating has a certain capacity, which can improve the performance of the negative electrode sheet and increase the capacity of the negative electrode sheet. In addition, the specific surface area of the layered multi-metal oxide is relatively large or it has a porous structure, and its stability is relatively high, which can be used to improve the ion diffusion rate of the negative electrode sheet while ensuring its cycle stability, and thus is conducive to improving the cycle performance of the battery using this negative electrode sheet. In addition, the layered multi-metal oxide in the second negative electrode coating has a layered structure and a relatively large interlayer spacing. During charging, it is beneficial to the rapid transmission of sodium ions on the surface of the negative electrode sheet, which is beneficial to improving the fast charging performance of the battery.
[0053] Furthermore, through the arrangement of the layered multi-metal oxide in the second negative electrode coating, the negative electrode sheet improves the capacity, ion diffusion rate, cycle stability, or the transmission speed of sodium ions, so that the capacity, cycle stability, and fast charging performance of the battery using this negative electrode sheet can be improved.
[0054] Additional aspects and advantages of the present application will be given in part in the following description, and in part will become obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION
[0055] The present application is further described below in conjunction with specific embodiments. It should be understood that these embodiments of the present application are only used to illustrate the present application and are not used to limit the scope of the present application.
[0056] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0057] If there is no special description, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution. If there is no special description, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.
[0058] If there is no special description, all steps of the present application can be performed sequentially or randomly, preferably sequentially. If there is no special description, the "include" and "comprising" mentioned in the present application represent open or closed forms. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0059] As mentioned in the background technology, the sodium ion battery in the related art has the characteristics of abundant resources, easy access to sodium and low price, and great price advantage. However, the negative electrode plate in the existing sodium ion battery still has certain shortcomings. In addition, in sodium ion batteries, positive electrode materials, as a key component of cost reduction of sodium ion batteries, have attracted much attention in recent years. Among them, Prussian blue positive electrode materials have attracted the favor of many researchers due to their low cost, easy access, simple process and high safety. However, Prussian blue sodium ion batteries have the following problems: First, the coordinated water in the lattice of Prussian blue positive electrode materials may be transferred to the electrolyte, electrochemical decomposition occurs, resulting in the destruction of the electrolyte, affecting the electrochemical performance of the battery, and even causing safety hazards; second, during the use of Prussian blue material sodium ion batteries, transition metals may dissolve, affecting the negative electrode SEI film, and then affecting the electrochemical performance of the battery; third, Prussian blue positive electrode material sodium ion batteries have poor fast charging performance, which is not conducive to the promotion and application of such batteries. Therefore, effective technical means are needed to improve the above-mentioned problems of sodium ion batteries containing Prussian blue-based positive electrode materials.
[0060] The inventors of this application have found through research that by improving the structure or composition of the negative electrode plate, not only can some problems of the negative electrode plate itself be improved, but also the electrochemical performance of the sodium ion battery using the Prussian blue positive electrode material can be improved. Thus, the inventors of this application have developed a suitable negative electrode plate, which can not only improve the capacity, ion diffusion rate and other properties of the negative electrode plate, but also can be used to improve the long cycle performance and safety performance of the sodium ion battery using the Prussian blue positive electrode material, thereby laying a more solid foundation for the commercial application of sodium ion batteries. Next, this application will be described in detail.
[0061] [Negative electrode]
[0062] In some embodiments, the present application provides a negative electrode plate, the negative electrode plate comprising:
[0063] current collector;
[0064] A first negative electrode coating is disposed on at least one side of the current collector along the thickness direction, and the first negative electrode coating includes a negative electrode active material; and
[0065] The second negative electrode coating is disposed on a surface of the first negative electrode coating away from the current collector. The second negative electrode coating comprises a layered multi-metal oxide, which contains at least two metal elements.
[0066] The provided negative electrode sheet has a multilayer structure, which includes a current collector, a first negative electrode coating and a second negative electrode coating which are stacked in sequence, that is, the first negative electrode coating is disposed on at least one side surface of the current collector, and the second negative electrode coating is disposed on the surface of the first negative electrode coating. The first negative electrode coating may be a conventional negative electrode coating (also referred to as a negative electrode active material layer), and the second negative electrode coating may be used as a multifunctional coating to improve the electrochemical performance of the negative electrode sheet.
[0067] The above-mentioned “the first negative electrode coating is disposed on at least one side surface of the current collector along the thickness direction” means that the first negative electrode coating can be disposed on one surface of the current collector along its own thickness direction, or on two surfaces of the current collector along its own thickness direction. The “surface” here can be the entire area of the current collector, or a partial area of the current collector. For example, in this embodiment, the surface can be a partial area of the current collector, and the remaining area of the current collector can be used to connect the pole ear. This application has no special restrictions on this, as long as the purpose of this application can be achieved.
[0068] As an example, the current collector has two surfaces opposite to each other in its thickness direction, and the first negative electrode coating is disposed on the two opposite surfaces of the current collector. Further, the second negative electrode coating is formed on the surfaces of the first negative electrode coating on both sides. It is understood that, in other embodiments, the first negative electrode coating may also be stacked on any one of the two surfaces of the current collector.
[0069] In the present application, in the negative electrode sheet, the material of the current collector is not specifically limited.
[0070] In the present application, in the negative electrode plate, the second negative electrode coating contains a layered multi-metal oxide, which contains two or more metal elements. Compared with a single metal oxide, the layered multi-metal oxide has a strong coupled electric field through the combination of two or more metal elements, which can accelerate the migration of electrons and speed up the electrochemical reaction kinetics, thereby helping to improve the electrochemical performance of the negative electrode plate using the layered multi-metal oxide.
[0071] Furthermore, the layered multi-metal oxide satisfies at least one of the following characteristics:
[0072] (I) The capacity of layered multi-metal oxides is ≥100 mAh / g;
[0073] (II) Specific surface area of layered multi-metal oxides ≥ 100 m 2 / g;
[0074] (III) Layered multi-metal oxides have a porous structure;
[0075] (IV) The interlayer spacing of the layered multi-metal oxide is ≥0.15nm.
[0076] Preferably, the layered multinary metal oxide satisfies all of the above characteristics, that is, the layered multinary metal oxide satisfies four of the above characteristics.
[0077] In some embodiments, the capacity of the layered multi-metal oxide is ≥100mAh / g; preferably, the capacity of the layered multi-metal oxide is 100-800mAh / g; more preferably, the capacity of the layered multi-metal oxide is 100-750mAh / g; for example, the capacity of the layered multi-metal oxide can be 100mAh / g, 150mAh / g, 170mAh / g, 200mAh / g, 300mAh / g, 500mAh / g, 700mAh / g, 720mAh / g, 750mAh / g, 800mAh / g or greater than 800mAh / g, etc. By including a layered multi-metal oxide with a certain capacity in the second negative electrode coating of the negative electrode sheet, the performance of the negative electrode material in the negative electrode sheet can be improved, which is conducive to improving the capacity of the negative electrode sheet.
[0078] In some embodiments, the specific surface area of the layered multi-metal oxide is ≥ 100 m 2 / g; preferably, the specific surface area of the layered multi-metal oxide is 100 to 200 m 2 / g; More preferably, the specific surface area of the layered multi-metal oxide is 120 to 170 m 2 / g; For example, the specific surface area of the layered multi-metal oxide can be 100m 2 / g, 120m 2 / g, 130m 2 / g, 140m 2 / g, 150m 2 / g, 160m 2 / g, 170m 2 / g, 200m 2 / g or greater than 200m 2 / g, etc. By making the second negative electrode coating of the negative electrode sheet contain a large specific surface area (e.g., not less than 100m 2 / g or not less than 120m 2 / g) of layered multi-metal oxides can provide more active sites, which is beneficial to improve the ion diffusion rate while ensuring the cycle stability of the battery.
[0079] In some embodiments, the layered multi-metal oxide has a porous structure. Preferably, the pore size range of the porous structure is 10nm to 20nm; more preferably, the pore size range of the porous structure is 14nm to 16nm. For example, the pore size of the porous structure can be any point value of 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm, 20nm or any range value between two of them. By making the second negative electrode coating of the negative electrode plate contain a layered multi-metal oxide with a porous structure, and making the pore size of the porous structure within the above-mentioned appropriate range, the appropriate pore size is easy to transmit ions and electrons while having a relatively stable structure, thereby improving the electrochemical reaction kinetics, and facilitating the improvement of the ion diffusion rate while ensuring the cycle stability of the battery.
[0080] Therefore, in the negative electrode plate of the present application, by making the second negative electrode coating contain a layered multi-metal oxide with a certain capacity, a large specific surface area and a porous structure, the performance of the negative electrode material in the negative electrode plate can be improved, and the capacity of the negative electrode plate can be increased. Through its porous, large specific surface area and high stability, the ion diffusion rate is increased while ensuring the cycle stability of the battery.
[0081] In some embodiments, the interlayer spacing of the layered multi-metal oxide is ≥ 0.15nm; preferably, the interlayer spacing of the layered multi-metal oxide is 0.2nm to 1.0nm; more preferably, the interlayer spacing of the layered multi-metal oxide is 0.3nm to 0.8nm. For example, the interlayer spacing of the layered multi-metal oxide can be 0.15nm, 0.2nm, 0.3nm, 0.4nm, 0.5nm, 0.6nm, 0.7nm, 0.8nm, 0.9nm, etc. The provided layered multi-metal oxide has a layered structure and a wide interlayer spacing (preferably 0.3 to 0.8nm), and the sodium ion radius is 0.102nm, so that during charging, it is beneficial to the rapid transmission of sodium ions on the negative electrode surface, which is beneficial to improve the fast charging performance of the battery.
[0082] It should be noted that the present application does not limit the test method for the specific surface area, interlayer spacing, pore size, etc. of the layered multinary metal oxide, and any method known in the art can be used for testing. For example, the specific surface area of the layered multinary metal oxide and the pore size of the porous structure can be obtained by testing with a porosity analyzer (specific surface area and porosity analyzer); the interlayer spacing of the layered multinary metal oxide can be obtained by testing with an X-ray diffractometer.
[0083] In some preferred embodiments, the provided negative electrode plate is used in a sodium ion battery, and the positive electrode active material in the sodium ion battery adopts a Prussian blue positive electrode material. Furthermore, the negative electrode plate of the present application can not only utilize the characteristics of the above-mentioned layered multi-metal oxides, such as certain capacity, porous structure, large specific surface area, wide interlayer spacing, and high stability, to improve the performance of the negative electrode material, increase the capacity, increase the ion diffusion rate, and ensure the cycle stability of the battery, increase the transmission speed of sodium ions on the surface of the negative electrode plate, and improve the fast charging performance of the battery; moreover, the negative electrode plate of the present application can also utilize the above-mentioned layered multi-metal oxides to absorb free water in the Prussian blue positive electrode material, and the layered multi-metal oxides become layered multi-metal hydroxides after absorbing water, and the layered multi-metal hydroxides have certain flame retardancy, which can be used to improve the safety and cycle life of the positive electrode material. At the same time, the layered multi-metal oxide and the layered multi-metal hydroxide formed after absorbing water have a strong adsorption effect on metal ions, which can be used to solve the phenomenon of thickening of the negative electrode SEI film caused by the dissolution of transition metals, ensure the performance of electrical performance, and further improve the safety and service life of the battery. Furthermore, the provided negative electrode plate can effectively improve the above-mentioned problems (such as safety problems, transition metal dissolution problems, poor fast charging performance, etc.) of the sodium ion battery containing Prussian blue positive electrode materials through the provision of the layered multi-metal oxide in the second negative electrode coating.
[0084] In some embodiments, the layered multi-metal oxide has a general chemical formula of M1 2+x M2 3+ y O z , M1 and M2 are selected from transition metal elements, wherein 0.4≤x≤0.8, 0.2≤y≤0.4, and z=(2x+3y) / 2. Optionally, x+y=1. It is worth noting that x, y and z need to satisfy charge balance.
[0085] The layered multi-metal oxide comprises M1 metal element and M2 metal element, M1 and M2 can be selected from transition metal elements, and M1 is selected from transition metal elements with positive divalence, and M2 is selected from transition metal elements with positive trivalence. In the present application, the chemical formula of the layered multi-metal oxide can be recorded as M1M2-LDO.
[0086] It should also be noted that in M1M2-LDO, the value ranges of x, y and z mentioned above can satisfy the above ranges. The specific values of x, y and z can be selected and set according to the actual application situation, as long as they satisfy the above ranges. This application does not limit this.
[0087] In some embodiments, M1 includes but is not limited to at least one of Ni, Zn, Mn, Mg, Cu or Co, M2 includes but is not limited to at least one of Fe, Bi, Al, V or Co, and M1 and M2 are not simultaneously selected from Co. That is, in the present application, the layered multi-metal oxide can be selected from metal oxides formed by at least two of the elements Ni, Zn, Mn, Fe, Mg, Cu, Co, Bi, Al, and V. The layered multi-metal oxide has a stronger coupling electric field than a single metal oxide, which can accelerate the migration of electrons and speed up the electrochemical reaction kinetics.
[0088] Preferably, M1 is selected from at least one of Ni, Zn, Mn or Co; more preferably, M1 is selected from at least one of Ni or Co. Preferably, M2 is selected from at least one of Fe, Al or Co; more preferably, M2 is selected from at least one of Fe or Co. Exemplarily, the layered multi-metal oxide may be NiFe-LDO, NiCo-LDO, CoFe-LDO or NiCoFe-LDO.
[0089] By using the above-mentioned Ni, Co, Fe and other transition metal elements to form a layered multi-metal oxide, the atomic radius of the metal elements is similar, the product is easy to prepare and the morphology is easy to control, and at the same time the synergistic effect between the metals is strong, which is conducive to the transfer of electrons and ions.
[0090] In some embodiments, the first negative electrode coating layer further includes a first binder and a first conductive agent, that is, the first negative electrode coating layer includes a negative electrode active material, a first binder and a first conductive agent.
[0091] In some embodiments, the second negative electrode coating further includes a second binder and a second conductive agent, that is, the second negative electrode coating includes a layered multinary metal oxide, a second binder and a second conductive agent. The second binder in the second negative electrode coating is used to bind the layered multinary metal oxide and the second conductive agent together, and at the same time, bind the first negative electrode coating and the second negative electrode coating.
[0092] It should be noted that in the negative electrode sheet, the specific type of the negative electrode active material is not limited and can be set according to conventional selection in the art.
[0093] As an example, in some embodiments, the negative electrode active material includes, but is not limited to, at least one of graphite, soft carbon or hard carbon. The graphite may be artificial graphite, natural graphite, modified graphite or the like.
[0094] In the present application, the negative electrode active material may be a negative electrode material known in the prior art. For example, the negative electrode active material may be graphite, soft carbon, hard carbon, a combination of graphite and soft carbon, a combination of graphite and hard carbon, or a combination of soft carbon and hard carbon.
[0095] It should be noted that there is no limitation on the structure and material selection of the negative electrode sheet not specifically described, and the negative electrode sheet can be configured according to conventional selections in the art.
[0096] As an example, in some embodiments, the first conductive agent includes, but is not limited to, at least one of conductive carbon black (Super P), graphene, conductive graphite, conductive carbon tubes, or conductive carbon fibers.
[0097] In some embodiments, the second conductive agent includes, but is not limited to, at least one of conductive carbon black (Super P), graphene, conductive graphite, conductive carbon tubes, or conductive carbon fibers.
[0098] Among them, the above-mentioned conductive carbon black includes acetylene black, Ketjen black, etc. The above-mentioned conductive carbon tube includes carbon nanotube, carbon microtube, etc. The above-mentioned conductive carbon fiber includes vapor-grown carbon fiber.
[0099] In the present application, the first conductive agent and the second conductive agent may be of the same type, or may be of different types, and this is not limited.
[0100] In addition, in other embodiments, any conductive agent known in the art that can be used in negative electrode sheets can also be used, which will not be listed here one by one.
[0101] Preferably, the first conductive agent and the second conductive agent are acetylene black or Ketjen black, which have low density and large specific surface area, high adhesion with negative electrode materials with large specific surface area, and are beneficial to the performance of porous materials.
[0102] In some embodiments, the first binder includes, but is not limited to, one or more of polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR), sodium hydroxymethyl cellulose (CMC), polyacrylic acid (PAA), polyacrylate (LA), polyvinyl alcohol, polytetrafluoroethylene, polyethylene oxide, carboxypropyl methylcellulose or hexafluoropropylene.
[0103] In some embodiments, the second binder includes, but is not limited to, one or more of polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA), polyacrylate (LA), polyvinyl alcohol, polytetrafluoroethylene, polyethylene oxide, carboxypropyl methylcellulose or hexafluoropropylene.
[0104] In the present application, the first adhesive and the second adhesive may be of the same type, or may be of different types, and this is not limited.
[0105] Preferably, the first binder and the second binder are selected from one or more of PVDF, SBR, CMC, PAA, and LA; more preferably, the first binder and the second binder are selected from one or more of CMC and PAA. CMC and PAA contain not only hydroxyl functional groups (-OH) but also carboxyl functional groups, which are beneficial to the improvement of the specific surface area and the fluidity of the porous material slurry.
[0106] In some embodiments, in the first negative electrode coating, the mass ratio of the negative electrode active material, the first conductive agent and the first binder is (90-94):(1-6):(2-4), such as 90:6:4, 92:5:3, 93:4:4, 94:3:3, etc.
[0107] In some embodiments, in the second negative electrode coating, the mass ratio of the layered multi-metal oxide, the second conductive agent and the second binder is (90-94):(2-6):(2-4), such as 90:6:4, 92:5:3, 93:4:4, 94:3:3, etc.
[0108] Preferably, the mass ratio of the layered multi-metal oxide to the second conductive agent is (90-94):(3-4).
[0109] Preferably, the mass ratio of the layered multi-metal oxide to the second binder is (90-94):(3-3.5).
[0110] It is understandable that the mass ratio of the negative electrode active material, the first conductive agent and the first binder, and the mass ratio of the layered multinary metal oxide, the second conductive agent and the second binder are related to the electrical performance of the corresponding battery. By controlling the ratio of each substance in the first negative electrode coating and the second negative electrode coating within the above range, the role of the negative electrode active material and the layered multinary metal oxide can be fully utilized, and the cycle performance and fast charging performance of the negative electrode sheet can be effectively improved.
[0111] In addition, in the present application, if the content of the layered multi-metal oxide in the second negative electrode coating is too little, such as less than 90 mass %, it will not be able to effectively improve the performance of the negative electrode material, increase the ion diffusion rate while ensuring its cycle stability, and improve the fast charging performance; if the content of the layered multi-metal oxide in the second negative electrode coating is too large, such as greater than 94 mass %, it will reduce the amount of binder, etc., affecting the bonding effect and other properties of the first negative electrode coating and the second negative electrode coating.
[0112] In some embodiments, the thickness of the second negative electrode coating on one side of the current collector is 2μm to 6μm. As an example, the thickness of the second negative electrode coating can be any point value of 2μm, 3μm, 4μm, 5μm, 6μm, or a range value between any two. If the thickness of the second negative electrode coating is too thin, such as less than 2μm, it will not be able to effectively improve the performance of the negative electrode material, increase the ion diffusion rate while ensuring its cycle stability, and improve the fast charging performance; if the thickness of the second negative electrode coating is too thick, such as greater than 6μm, it will affect the electrochemical reaction and increase the impedance.
[0113] In some embodiments, the thickness ratio of the second negative electrode coating to the first negative electrode coating is 1:(10-30). For example, the thickness ratio of the second negative electrode coating to the first negative electrode coating may be 1:10, 1:15, 1:20, 1:25, 1:30, etc.
[0114] In the present application, since the layered multi-metal oxide has the characteristics of being porous and having a large specific surface area, if the thickness of the second negative electrode coating containing the layered multi-metal oxide is too thick, the electron transmission distance will increase, the electronic resistance will increase, and the rate performance will decrease, affecting the performance of negative electrode active materials such as hard carbon; if the thickness of the second negative electrode coating containing the layered multi-metal oxide is too thin, the performance improvement of the entire battery will not be obvious, and the overall electrical performance and safety of the battery cell cannot be further guaranteed and optimized, which is not conducive to the long cycle of the battery.
[0115] [Method for preparing negative electrode sheet]
[0116] In some embodiments, the present application provides a method for preparing a negative electrode sheet, which comprises the following steps:
[0117] Coating a first negative electrode slurry on at least one side of the current collector to obtain a first negative electrode coating;
[0118] Coating a second negative electrode slurry on the surface of the first negative electrode coating to obtain a second negative electrode coating;
[0119] The first negative electrode coating layer includes a negative electrode active material, and the second negative electrode coating layer includes a layered multi-metal oxide.
[0120] It should be understood that all the features and advantages described above for the “negative electrode sheet” are also applicable to the “method for preparing the negative electrode sheet” and will not be described in detail here.
[0121] During the preparation process of the negative electrode plate of the present application, a layered multinary metal oxide can be first prepared, and then a second negative electrode slurry containing the layered multinary metal oxide and a first negative electrode slurry containing a negative electrode active material can be prepared. Then, by coating, drying, etc., a first negative electrode coating and a second negative electrode coating are formed respectively to obtain a negative electrode plate.
[0122] Illustratively, in some embodiments, the preparation of the layered multi-metal oxide includes: mixing M1 salt, M2 salt, water and urea, and obtaining the layered multi-metal oxide after hydrothermal reaction, washing, drying, calcining and ball milling.
[0123] In the preparation process of the above-mentioned layered multinary metal oxide, a hydrothermal reaction is first performed. During the hydrothermal reaction, the material after the mixture of M1 salt, M2 salt, water and urea can react to generate a layered multinary metal hydroxide. Further, after the hydrothermal reaction, the obtained material can be washed to remove impurities, and after drying, the generated layered multinary metal hydroxide is calcined to prepare a layered multinary metal oxide powder. Then, the obtained layered multinary metal oxide powder is ball-milled to obtain a layered multinary metal oxide of a target size (such as nanometer level).
[0124] In the present application, the size of the layered multinary metal oxide is nanometer-scale, so that there are more active sites and faster reaction kinetics. There is no restriction on the specific size of the layered multinary metal oxide, and it can be selected and set according to actual needs, as long as it is nanometer-scale. Generally, since the layered multinary metal oxide is generally a micrometer-sized sheet material, the volume expansion is large during a long cycle, which affects the lifespan. Therefore, when preparing the second negative electrode coating, the present application uses a high-energy ball milling method to prepare the micrometer-scale layered multinary metal oxide into a nanometer-sized material, which can effectively reduce the impact of volume expansion.
[0125] In some embodiments, in the raw materials for preparing the layered multinary metal oxide, the anions of the M1 salt and the M2 salt respectively include at least one of nitrate ion, sulfate ion, chloride ion or acetate ion.
[0126] In some embodiments, in the raw materials for preparing layered multi-metal oxides, the M1 element of the M1 salt includes at least one of Ni, Zn, Mn, Mg, Cu or Co, and the M2 element of the M2 salt includes at least one of Fe, Bi, Al, V or Co.
[0127] In some embodiments, the molar ratio of M1 salt, M2 salt and urea is (5-7): (0.5-1.5): 10. Preferably, the molar ratio of M1 salt, M2 salt and urea is (5-7): (0.9-1.2): 10. For example, the molar ratio of M1 salt, M2 salt and urea is 5:1:10, 6:1:10, 7:1:10, 7:1.1:10, etc.
[0128] It should be understood that during the preparation of the layered multi-metal oxide, the amounts of the raw materials M1 salt and M2 salt added may be slightly different from the ratio of M1 and M2 in the final layered multi-metal oxide. This is because in order to improve the reaction efficiency or the production rate, it is necessary to make some of the added raw materials slightly excessive. After the reaction, the excess M1 salt or M2 salt can be removed by washing and other steps to obtain a layered multi-metal oxide containing the target ratio of M1 and M2.
[0129] In some embodiments, the mass ratio of M1 salt to water is (0.8-1.2): 20. For example, the mass ratio of M1 salt to water is 0.8:20, 0.9:20, 1:20, 1.2:20, etc.
[0130] In some embodiments, the temperature of the hydrothermal reaction is 120°C to 180°C, and the time of the hydrothermal reaction is 8h to 12h. As an example, the temperature of the hydrothermal reaction can be 120°C, 130°C, 140°C, 150°C, 160°C, 180°C, etc., and of course it can also be other values within the above range, which is not limited here; the hydrothermal reaction time can be 8h, 9h, 10h, 11h, 12h, etc., and of course it can also be other values within the above range, which is not limited here. By controlling the temperature and time of the hydrothermal reaction within the above appropriate range, a layered multi-metal hydroxide with good performance can be prepared.
[0131] The specific operation methods of the washing and drying steps after the hydrothermal reaction can be conventional, for example, washing with solvents such as water and alcohol, and then drying at 50° C. to 100° C. for 10 h to 48 h.
[0132] In some embodiments, the calcination temperature is 450°C to 500°C, and the calcination time is 1h to 2h. As an example, the calcination temperature can be 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, etc., and of course it can also be other values within the above range, which is not limited here; the calcination time can be 1h, 1.5h, 2h, etc., and of course it can also be other values within the above range, which is not limited here. Layered multi-metal oxides can be prepared by calcining layered multi-metal hydroxides. If the calcination temperature is too high, such as greater than 500°C, the layered multi-metal oxide structure collapses and cannot be restored; if the calcination temperature is too low, such as below 450°C, layered multi-metal oxides cannot be formed.
[0133] In some embodiments, the ball milling speed is 50-70r / min, and the ball milling time is 12h-24h. As an example, the ball milling speed can be 50r / min, 60r / min, 70r / min, etc., and of course it can also be other values within the above range, which is not limited here; the ball milling time can be 12h, 16h, 18h, 20h, 22h, 24h, etc., and of course it can also be other values within the above range, which is not limited here. By controlling the speed and time of ball milling, suitable nano-sized layered multi-metal oxides can be prepared, so that there are more active sites and faster reaction kinetics.
[0134] In the present application, since the layered multi-metal oxide is calcined from layered metal hydroxide, it has the properties of large specific surface area and porosity. Preferably, the specific surface area of the layered multi-metal oxide is in the range of 120 to 170 m 2 / g, the pore size of the porous structure ranges from 10 to 20 nm. More preferably, the ball mill speed is 55 to 65 r / min, and the ball milling time is 16 to 20 h. In this way, after ball milling, the original layered structure is retained with a larger specific surface area and a suitable pore size. The preferred specific surface area of the layered multi-metal oxide ranges from 140 to 170 m 2 / g, the pore size range of the porous structure is 14 to 16 nm, so that a larger specific surface area can provide more active sites. The appropriate pore size facilitates the transmission of ions and electrons while having a more stable structure, thereby improving the kinetics of electrochemical reactions.
[0135] In the present application, preferably, the prepared layered multi-metal oxide is NiFe-LDO, NiCo-LDO, CoFe-LDO or NiCoFe-LDO. The atomic radius of the metal elements in these layered multi-metal oxides is similar, the products are easy to prepare and the morphology is easy to control, and the synergistic effect between the metals is strong, which is conducive to the transfer of electrons and ions.
[0136] As an example, the preparation of layered multi-metal oxides specifically includes: mixing M1 salt, M2 salt, water and urea, such as mixing at least two of Ni, Zn, Mn, Fe, Mg, Cu, Co, Bi, Al, V salts (nitrates, sulfates, chlorides, acetates) with urea, and performing a hydrothermal reaction at a temperature of 120°C to 180°C for 8h to 12h to prepare a layered multi-metal hydroxide; then, placing it in a ceramic boat and placing it in a tubular furnace, calcining it at a temperature of 450 to 500°C for 1 to 2h to prepare a layered multi-metal oxide powder; then, adding the prepared powder to a planetary ball mill, setting the ball mill speed to 50 to 70r / min, and the ball milling time to 12 to 24h to prepare a nano-sized layered multi-metal oxide.
[0137] In some embodiments, the preparation of the negative electrode sheet specifically includes:
[0138] S1, respectively preparing a first negative electrode slurry and a second negative electrode slurry;
[0139] S2, uniformly coating the first negative electrode slurry on the surface of the current collector, and after drying, forming a first negative electrode coating on the surface of the current collector; wherein, optionally, the coating thickness of the first negative electrode coating is 40 μm to 60 μm;
[0140] S3. Apply the second negative electrode slurry on the first negative electrode coating, and after drying, form a second negative electrode coating on the surface of the first negative electrode coating to obtain a negative electrode plate. Optionally, the ratio of the coating thickness of the second negative electrode coating to the coating thickness of the first negative electrode coating is 1: (10-30). By controlling the ratio of the coating thickness of the second negative electrode coating to the coating thickness of the first negative electrode coating within the above range, it helps to ensure the electrochemical performance of the battery. This is because the layered multi-metal oxide has the characteristics of being porous and having a large specific surface area. If the thickness of the second negative electrode coating is too thick, the electron transmission distance increases, the electronic resistance increases, and the rate performance decreases, which affects the performance of negative active materials such as hard carbon. If the thickness of the second negative electrode coating is too thin, the performance improvement of the whole battery is not obvious.
[0141] Optionally, in step S1, the preparation of the first negative electrode slurry includes: uniformly mixing the negative electrode active material, the first conductive agent and the first binder in a solvent to obtain the first negative electrode slurry.
[0142] Optionally, in step S1, the preparation of the second negative electrode slurry includes: uniformly mixing the layered multi-metal oxide, the second conductive agent and the second binder in a solvent to obtain the second negative electrode slurry.
[0143] The components and contents of the negative electrode active material, the first conductive agent, the first binder, the second conductive agent, the second binder, etc. described herein refer to the first aspect and will not be described in detail here.
[0144] The solvent in the first negative electrode slurry and the second negative electrode slurry may be a conventional solvent for preparing negative electrode slurry in the art, such as water, an organic solvent, etc., and is not limited thereto.
[0145] Optionally, in steps S2 and S3, the drying temperature is 100° C. to 150° C., and the drying time is 0.5 h to 12 h. In steps S2 and S3, the purpose of drying is to remove moisture from the negative electrode sheet.
[0146] [Battery]
[0147] In some embodiments, a battery is provided, which includes the aforementioned negative electrode plate.
[0148] Since the battery includes the negative electrode plate provided in the embodiment of the present application, it can exhibit good electrochemical properties, such as a higher first discharge specific capacity, good cycle stability and good fast charging performance.
[0149] In the present application, the battery may be a sodium ion battery. The battery stacking type is, for example, a wound or laminated battery, and the structural type is, for example, a square shell (aluminum shell, steel shell, etc.) battery, a soft pack battery or a cylindrical battery, etc., without specific limitation. The battery has a high capacity, good cycle effect, long service life, and good fast charging performance.
[0150] In some embodiments, the battery further comprises a positive electrode sheet, an electrolyte and a separator. That is, the battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator.
[0151] In some embodiments, the positive electrode sheet includes a positive electrode coating, the positive electrode coating includes a positive electrode active material, and the positive electrode active material includes a Prussian blue-based positive electrode material.
[0152] Exemplarily, the positive electrode sheet includes a positive electrode current collector and a positive electrode coating disposed on at least one surface of the positive electrode current collector, the positive electrode coating including a positive electrode active material, and the positive electrode active material including a Prussian blue positive electrode material. As an example, the positive electrode current collector has two surfaces opposite to each other in its own thickness direction, and the positive electrode coating is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0153] In this embodiment, there is no limitation on the materials and structures of the positive electrode sheet, the positive current collector, the conductive agent, the binder in the positive active material layer, and the like, and any positive electrode sheet structure and composition known in the art that can be used for secondary batteries can be selected.
[0154] In particular, the positive electrode active material in the positive electrode sheet of the embodiments of the present application may include Prussian blue-based positive electrode materials. With the negative electrode sheet provided by the present application, in combination with a sodium-ion battery including Prussian blue-based positive electrode materials, the layered multi-metal oxide in the negative electrode sheet can be used to absorb the free water in the Prussian blue-based positive electrode materials. After absorbing water, the layered multi-metal oxide becomes a layered multi-metal hydroxide, which has a certain flame retardancy and can be used to improve the safety and cycle life of the positive electrode material. At the same time, the layered multi-metal oxide and the layered multi-metal hydroxide formed after water absorption have a strong adsorption effect on metal ions, which can be used to solve the phenomenon of thickening of the negative electrode SEI film caused by the dissolution of transition metals, ensure the performance of the electrical properties, and further improve the battery safety and service life. Furthermore, it can effectively improve the above problems existing in sodium-ion batteries containing Prussian blue-based positive electrode materials (such as safety problems, transition metal dissolution problems, poor fast charging performance, etc.).
[0155] In some embodiments, the chemical general formula of the Prussian blue-based positive electrode material is Na x M3[M4(CN)6] y ·zH2O, 0 < x ≤ 2, 0.8 ≤ y ≤ 1, 0 < z ≤ 20, where M3 and M4 are respectively selected from transition metal elements.
[0156] Optionally, M3 and M4 can be selected from one or more of Fe, Mn, Cu, Ni, Co, Zn or Cr.
[0157] In some embodiments, the positive electrode coating further includes a positive electrode conductive agent and a positive electrode binder, that is, the positive electrode coating includes a positive electrode active material, a positive electrode conductive agent and a positive electrode binder. In this positive electrode coating, the specific types of the positive electrode conductive agent and the positive electrode binder are not limited and can be set according to the conventional selection in the art. As an example, the positive electrode conductive agent includes, but is not limited to, at least one of conductive carbon black, graphene, conductive graphite, carbon nanotubes or conductive carbon fibers. The above conductive carbon black includes acetylene black, Ketjen black, etc. The above carbon nanotubes include carbon nanotubes, carbon microtubes, etc. The above conductive carbon fibers include vapor-grown carbon fibers. The positive electrode binder includes, but is not limited to, one or more of polyvinylidene fluoride, styrene-butadiene rubber, sodium carboxymethyl cellulose, polyacrylic acids, polyacrylates, polyvinyl alcohol, polytetrafluoroethylene, polyethylene oxide, carboxypropyl methyl cellulose or hexafluoropropylene.
[0158] Optionally, the mass ratio of the positive electrode active material, the positive electrode conductive agent and the positive electrode binder is (90 - 94):(1 - 6):(2 - 4), such as 90:6:4, 92:5:3, 93:4:4, 94:3:3, etc.
[0159] Optionally, the preparation of the positive electrode sheet includes: first preparing a positive electrode slurry, then uniformly coating the positive electrode slurry on the positive electrode current collector, and after drying, forming a positive electrode coating on the surface of the positive electrode current collector to obtain a positive electrode sheet. For example, after the positive electrode slurry is prepared, the coating machine parameters are set so that the coating thickness is 50 μm to 60 μm (such as 55 μm), and the positive electrode slurry is uniformly coated on the positive electrode current collector aluminum foil. After the coating is completed, the electrode sheet is dried at 110° C. for 0.5 h to obtain a positive electrode sheet.
[0160] Wherein, optionally, the preparation of the positive electrode slurry includes: uniformly mixing the positive electrode active material, the positive electrode conductor and the positive electrode binder in a solvent to obtain the positive electrode slurry.
[0161] Optionally, during the preparation of the positive electrode sheet, the drying temperature is 100° C. to 150° C., and the drying time is 0.5 h to 12 h. The purpose of drying is to remove moisture from the positive electrode sheet.
[0162] In some embodiments, in the battery, the diaphragm includes, but is not limited to, a polypropylene diaphragm (PP), a polyethylene diaphragm (PE), and a multilayer composite diaphragm (PP / PE / PP). Preferably, the diaphragm is a PE diaphragm, so that the layered multi-metal oxide absorbs water to become a layered multi-metal hydroxide, and the layered multi-metal hydroxide is alkaline. The PE diaphragm has good chemical stability and can resist alkali corrosion. At the same time, the layered multi-metal hydroxide has good high temperature resistance, which makes up for the disadvantage of the poor heat resistance of the PE diaphragm.
[0163] It should also be noted that the battery of the present application is not limited to the specific material or type of the electrolyte, and the components and types that are known in the art and can be used for secondary batteries can be selected as long as the purpose of the present application can be achieved.
[0164] Since the battery and electronic device provided in the embodiments of the present invention adopt all the technical solutions of the above embodiments, they at least have all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.
[0165] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this area or the product instructions are used. If the manufacturer of the reagents, materials or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0166] Example 1
[0167] 1. Preparation of negative electrode sheet, including the following steps:
[0168] S1. Weigh hard carbon material, SP and PVDF respectively according to a mass ratio of 90:6:4, add NMP according to a mass ratio of hard carbon material to N-methylpyrrolidone (NMP) of 1:2.2, disperse at high speed, and mix evenly to obtain a first negative electrode slurry.
[0169] Layered multi-metal oxide (NiFe-LDO), acetylene black and CMC were weighed in a mass ratio of 93:4:3, and NMP was added in a mass ratio of NiFe-LDO to N-methylpyrrolidone (NMP) of 1:2, and the mixture was dispersed at a high speed and mixed evenly to obtain a second negative electrode slurry.
[0170] S2. Set the coating machine parameters so that the coating thickness is 40 μm, and evenly coat the first negative electrode slurry on the surface of the current collector aluminum foil. After the coating is completed, the electrode sheet is blown dry at 110° C. for 0.5 h to form a first negative electrode coating on the surface of the current collector to obtain electrode sheet A.
[0171] S3. Apply the second negative electrode slurry on the first negative electrode coating of the electrode sheet A so that the coating thickness of the second negative electrode coating is 2 μm. Blow dry the coated electrode sheet at 110° C. for 12 h to form a second negative electrode coating on the surface of the first negative electrode coating to obtain a negative electrode sheet.
[0172] In the above step S1, the preparation of the layered multi-metal oxide (NiFe-LDO) includes: weighing nickel nitrate, iron nitrate, and urea according to a molar ratio of 5:1:10, and the mass ratio of nickel salt to distilled water is 1:20, mixing nickel nitrate, iron nitrate, urea and distilled water, stirring for 30 minutes, and then pouring them into a reactor, placing the hydrothermal reactor in an oven, and performing a hydrothermal reaction at a temperature of 150°C for 10 hours to prepare a layered multi-metal hydroxide, collecting the sample with a high-speed centrifuge, and then The sample was washed three times with water and ethanol to remove excess impurities, and then dried in a drying oven at a constant temperature of 60°C for 24 hours to obtain a powder sample; then, it was placed in a ceramic boat and put into a tubular furnace, and calcined at a temperature of 450°C for 2 hours to prepare layered NiFe-LDO powder. The prepared powder was then added to a planetary ball mill, the ball mill speed was set to 60r / min, and the ball milling time was 18 hours to prepare a nano-sized layered multi-metal oxide, namely NiFe-LDO.
[0173] The capacity of the NiFe-LDO is about 728 mAh / g; the specific surface area is 165 m 2 / g; the pore size of the porous structure is 15nm; and the interlayer spacing is 0.45nm.
[0174] 2. The preparation of the positive electrode sheet includes the following steps:
[0175] Prussian blue positive electrode material Na and 1.73 Fe[Fe(CN)6]·3.8H2O, SP and PVDF, according to the Prussian blue cathode material Na 1.73 Fe[Fe(CN)6]·3.8H2O and NMP were added in a mass ratio of 1:2.2, and NMP was dispersed at high speed and mixed evenly to obtain a positive electrode slurry;
[0176] The coating machine parameters were set to make the coating thickness 35 μm, and the positive electrode slurry was evenly coated on the positive electrode current collector aluminum foil. After the coating was completed, the electrode sheet was dried by forced air at 110° C. for 0.5 h to obtain the positive electrode sheet.
[0177] Example 2
[0178] This embodiment is mainly used to illustrate the preparation of negative electrode plates when using different layered multi-metal oxides.
[0179] Example 2-1
[0180] The operation was carried out according to the method described in Example 1, except that:
[0181] The preparation of layered multi-metal oxide (NiCo-LDO) includes: nickel nitrate, cobalt nitrate, and urea are weighed according to a molar ratio of 6:1:10, the mass ratio of nickel salt to distilled water is 1:20, nickel nitrate, cobalt nitrate, urea and distilled water are mixed, stirred for 30 minutes, and then poured into a reactor, the hydrothermal reactor is placed in an oven, a hydrothermal reaction is carried out at a temperature of 160°C, the hydrothermal reaction time is 10 hours, a layered multi-metal hydroxide is prepared, a sample is collected by a high-speed centrifuge, and the sample is then washed with water. , and ethanol for three times to remove excess impurities, and then dried in a drying oven at a constant temperature of 60°C for 24 hours to obtain a powder sample; then, placed it in a ceramic boat and put it into a tubular furnace, and calcined it at a temperature of 450°C for 2 hours to prepare layered NiCo-LDO powder, and then added the prepared powder into a planetary ball mill, the ball mill speed was set to 64r / min, and the ball milling time was 18 hours to prepare a nano-sized layered multi-metal oxide, namely NiCo-LDO.
[0182] The capacity of the NiCo-LDO is about 720 mAh / g; the specific surface area is 149 m 2 / g; the pore size of the porous structure is 16nm; and the interlayer spacing is 0.43nm.
[0183] The rest are the same as in Example 1.
[0184] Example 2-2
[0185] The operation was carried out according to the method described in Example 1, except that:
[0186] The preparation of layered multi-metal oxide (NiCoFe-LDO) includes: weighing nickel nitrate, cobalt nitrate, iron nitrate and urea according to a molar ratio of 7:1:1:10, the mass ratio of nickel salt to distilled water is 1:20, mixing nickel nitrate, cobalt nitrate, iron nitrate, urea and distilled water, stirring for 30 minutes, and then pouring into a reactor, placing the hydrothermal reactor in an oven, performing a hydrothermal reaction at a temperature of 160°C, and the hydrothermal reaction time is 11 hours to prepare a layered multi-metal hydroxide, collecting a sample with a high-speed centrifuge, and then The sample was washed three times with water and ethanol to remove excess impurities, and then dried in a drying oven at a constant temperature of 60°C for 24 hours to obtain a powder sample; then, it was placed in a ceramic boat and put into a tubular furnace, and calcined at a temperature of 450°C for 1.5 hours to prepare layered NiCoFe-LDO powder, and then the prepared powder was added to a planetary ball mill, the ball mill speed was set to 62r / min, and the ball milling time was 19 hours to prepare a nano-sized layered multi-metal oxide, namely NiCoFe-LDO.
[0187] The capacity of the NiCoFe-LDO is about 718 mAh / g; the specific surface area is 158 m 2 / g; the pore size of the porous structure is 14nm; and the interlayer spacing is 0.41nm.
[0188] The rest are the same as in Example 1.
[0189] Example 2-3
[0190] The operation was carried out according to the method described in Example 1, except that:
[0191] The preparation of layered multi-metal oxide (NiCoFe-LDO) includes: weighing nickel nitrate, cobalt nitrate, iron nitrate and urea according to a molar ratio of 7:1:1:10, the mass ratio of nickel salt to distilled water is 1:20, mixing nickel nitrate, cobalt nitrate, iron nitrate, urea and distilled water, stirring for 30 minutes, and then pouring into a reactor, placing the hydrothermal reactor in an oven, performing a hydrothermal reaction at a temperature of 160°C, and the hydrothermal reaction time is 11 hours to prepare a layered multi-metal hydroxide, collecting a sample with a high-speed centrifuge, and then The sample was washed three times with water and ethanol to remove excess impurities, and then dried in a drying oven at a constant temperature of 60°C for 24 hours to obtain a powder sample; then, it was placed in a ceramic boat and put into a tubular furnace, and calcined at a temperature of 450°C for 1.5 hours to prepare layered NiCoFe-LDO powder, and then the prepared powder was added to a planetary ball mill, the ball mill speed was set to 70r / min, and the ball milling time was 24 hours to prepare a nano-sized layered multi-metal oxide, namely NiCoFe-LDO.
[0192] The capacity of the NiCoFe-LDO is about 718 mAh / g; the specific surface area is 169 m 2 / g; the pore size of the porous structure is 16nm; and the interlayer spacing is 0.41nm.
[0193] The rest are the same as in Example 1.
[0194] Embodiment 2-4
[0195] The operation was carried out according to the method described in Example 1, except that:
[0196] The preparation of layered multi-metal oxide (NiCoFe-LDO) includes: weighing nickel nitrate, cobalt nitrate, iron nitrate and urea according to a molar ratio of 7:1:1:10, respectively, and the mass ratio of nickel salt to distilled water is 1:20, mixing nickel nitrate, cobalt nitrate, iron nitrate, urea and distilled water, stirring for 30 minutes, and then pouring into a reactor, placing the hydrothermal reactor into an oven, performing a hydrothermal reaction at a temperature of 160°C, and the hydrothermal reaction time is 11 hours to prepare a layered multi-metal hydroxide, collecting the sample with a high-speed centrifuge, and then The sample was washed three times with water and ethanol to remove excess impurities, and then dried in a drying oven at a constant temperature of 60°C for 24 hours to obtain a powder sample; then, it was placed in a ceramic boat and put into a tubular furnace, and calcined at a temperature of 500°C for 1 hour to prepare a layered NiCoFe-LDO powder. The prepared powder was then added to a planetary ball mill, the ball mill speed was set to 50r / min, and the ball milling time was 12 hours to prepare a nano-sized layered multi-metal oxide, namely NiCoFe-LDO.
[0197] The capacity of the NiCoFe-LDO is about 718 mAh / g; the specific surface area is 142 m 2 / g; the pore size of the porous structure is 14nm; and the interlayer spacing is 0.41nm.
[0198] The rest are the same as in Example 1.
[0199] Example 3
[0200] This embodiment is mainly used to illustrate the preparation of negative electrode sheets and positive electrode sheets when the proportions of the substances in the first negative electrode slurry, the second negative electrode slurry or the positive electrode slurry are different.
[0201] Example 3-1
[0202] The operation was carried out according to the method described in Example 1, except that:
[0203] The hard carbon material, SP and PVDF were weighed respectively at a mass ratio of 94:4:2, and NMP was added at a mass ratio of the hard carbon material to NMP of 1:2.2, and the mixture was dispersed at a high speed and mixed evenly to obtain the first negative electrode slurry.
[0204] Layered multi-metal oxide (NiFe-LDO), acetylene black and CMC were weighed in a mass ratio of 93:3:4, and NMP was added in a mass ratio of NiFe-LDO to NMP of 1:2, and the mixture was dispersed at a high speed and mixed evenly to obtain a second negative electrode slurry.
[0205] Prussian blue cathode materials Na4Fe(CN)6·10H2O, SP and PVDF were weighed respectively in a mass ratio of 94:4:2, and NMP was added in an amount of 1:2.2 of the mass ratio of the Prussian blue cathode materials Na4Fe(CN)6·10H2O to NMP, and the cathode slurry was prepared after high-speed dispersion and uniform mixing.
[0206] The rest are the same as in Example 1.
[0207] Example 3-2
[0208] The operation was carried out according to the method described in Example 1, except that:
[0209] The hard carbon material, SP and PVDF were weighed respectively at a mass ratio of 92:5:3, and NMP was added at a mass ratio of the hard carbon material to NMP of 1:2.2, and the mixture was dispersed at a high speed and mixed evenly to obtain the first negative electrode slurry.
[0210] Layered multi-metal oxide (NiFe-LDO), acetylene black and CMC were weighed respectively at a mass ratio of 93:3.5:3.5, and NMP was added at a mass ratio of NiFe-LDO to NMP of 1:2, and the mixture was dispersed at a high speed and mixed evenly to obtain a second negative electrode slurry.
[0211] Prussian blue positive electrode material Na and 1.79 Fe[Fe(CN)6]·0.16H2O, SP and PVDF, according to the Prussian blue cathode material Na 1.79 Fe[Fe(CN)6]·0.16H2O and NMP were added in a mass ratio of 1:2.2, dispersed at a high speed, and mixed evenly to obtain a positive electrode slurry.
[0212] The rest are the same as in Example 1.
[0213] Example 3-3
[0214] The operation was carried out according to the method described in Example 1, except that:
[0215] Layered multi-metal oxide (NiFe-LDO), acetylene black and CMC were weighed at a mass ratio of 90:5:5, and NMP was added at a mass ratio of NiFe-LDO to NMP of 1:2, and the mixture was dispersed at a high speed and mixed evenly to obtain a second negative electrode slurry.
[0216] The rest are the same as in Example 1.
[0217] Embodiment 3-4
[0218] The operation was carried out according to the method described in Example 1, except that:
[0219] Layered multi-metal oxide (NiFe-LDO), acetylene black and CMC were weighed in a mass ratio of 94:3:3, and NMP was added in a mass ratio of NiFe-LDO to NMP of 1:2, and the mixture was dispersed at a high speed and mixed evenly to obtain a second negative electrode slurry.
[0220] The rest are the same as in Example 1.
[0221] Example 4
[0222] This embodiment is mainly used to illustrate the preparation of negative electrode sheets and positive electrode sheets when the thicknesses of the first negative electrode coating, the second negative electrode coating or the positive electrode coating are different.
[0223] Example 4-1
[0224] The operation was carried out according to the method described in Example 1, except that:
[0225] In the preparation of the negative electrode sheet, the coating thickness of the first negative electrode coating is 60 μm; the coating thickness of the second negative electrode coating is 4 μm.
[0226] In the preparation of the positive electrode sheet, the coating thickness of the positive electrode coating is 55 μm.
[0227] The rest are the same as in Example 1.
[0228] Example 4-2
[0229] The operation was carried out according to the method described in Example 1, except that:
[0230] In the preparation of the negative electrode sheet, the coating thickness of the first negative electrode coating is 50 μm; the coating thickness of the second negative electrode coating is 5 μm.
[0231] In the preparation of the positive electrode sheet, the coating thickness of the positive electrode coating is 45 μm.
[0232] The rest are the same as in Example 1.
[0233] Comparative Example 1
[0234] This comparative example is mainly used to illustrate the preparation of a negative electrode sheet when the second negative electrode coating is not provided on the negative electrode sheet.
[0235] The operation was performed according to the method described in Example 1, except that no second negative electrode coating was provided on the first negative electrode coating, that is, the negative electrode plate of Comparative Example 1 only included a current collector and the first negative electrode coating provided on the current collector.
[0236] Comparative Example 2
[0237] This comparative example is mainly used to illustrate the preparation of negative electrode plates when existing materials are used to replace layered multi-metal oxides.
[0238] The method described in Example 1 was followed, except that NiO was used to replace the layered multi-metal oxide;
[0239] The capacity of NiO is about 718 mAh / g; the specific surface area is 115 m 2 / g; the pore size of the porous structure is 22nm; and the interlayer spacing is 0.46nm.
[0240] Performance Testing
[0241] 1. Preparation of sodium ion batteries
[0242] (1) The positive electrode sheets prepared in the above-mentioned embodiments and comparative examples were respectively rolled, and the positive electrode sheets were punched into positive electrode sheets with a diameter of φ14 mm using a punching machine.
[0243] (2) The negative electrode sheets prepared in the above-mentioned embodiments and comparative examples were respectively rolled, and the negative electrode sheets were punched into negative electrode sheets with a diameter of φ14 mm using a punching machine.
[0244] (3) Provide PE diaphragm as isolation membrane.
[0245] (4) Providing an electrolyte, wherein the electrolyte is prepared by dissolving 1.0 mol / L NaPF6 in an organic solvent of diethylene glycol dimethyl ether.
[0246] (5) Assemble the full battery in the order of positive electrode shell, positive electrode sheet, separator, negative electrode sheet, nickel foam and negative electrode shell. Clamp the assembled full battery with insulating tweezers and place it on a packaging machine for sealing. Finally, let the packaged full battery stand for 24 hours to allow the electrolyte to fully infiltrate the electrode materials before conducting electrochemical tests.
[0247] 2. Test the electrochemical performance of the battery
[0248] (1) First-cycle discharge capacity test: The sodium ion batteries prepared in each embodiment and comparative example were respectively taken and first-cycle discharge capacity test was carried out under the test conditions of 0.2C rate, 4.8V charge cut-off voltage and 2.0V discharge cut-off voltage at 25°C.
[0249] (2) Test of discharge capacity after 1000 cycles and capacity retention rate after 1000 cycles: Take the sodium ion batteries prepared in each embodiment and comparative example respectively, discharge to 2.0V at 0.2C rate under 25°C environment, and continue to charge to 4.8V at 0.2C rate, which is a complete charge and discharge cycle, recorded as cycle 1. Repeat this process until the number of cycles is equal to 1000, and then end the test. The discharge capacity of the last cycle is the discharge capacity after 1000 cycles; the capacity retention rate after 1000 cycles = discharge capacity after 1000 cycles / discharge capacity in the first cycle*100%.
[0250] (3) 1C / 1C cycle life test: The sodium ion batteries prepared in each embodiment and comparative example were respectively taken and capacity divided under the test conditions of 0.2C rate, charge cut-off voltage of 4.8V and discharge cut-off voltage of 2.0V at 25°C. Then, a 1C / 1C cycle test was performed at 25°C (charge cut-off voltage of 4.8V and discharge cut-off voltage of 2.0V), and the number of cycles when the discharge specific capacity dropped to 0 was recorded.
[0251] (4) Test of charge transfer resistance of new battery: Use Autolab electrochemical workstation to test the charge transfer resistance of half-cell, with the test frequency of 0.01 Hz to 100 kHz.
[0252] (5) Test of sodium ion diffusion coefficient of new battery: Use CT2001A blue battery system to perform constant current intermittent titration test on half-cell with voltage range of 02.0~4.8V.
[0253] (6) Test of metal content of negative electrode after 1000 cycles: Take the negative electrode after 1000 cycles, scrape off the negative electrode material on the aluminum foil, and use an energy dispersive spectrometer to measure the metal content of the sample.
[0254] (7) 1C cycle third cycle full charge time test: record the time required for 1C charging to 4.8V after discharging to 2.0V in the third cycle of 1C cycle.
[0255] The test results are shown in Table 1 below.
[0256] Table 1
[0257]
[0258]
[0259]
[0260] It can be seen from Table 1 that, compared with Comparative Examples 1-2, the batteries prepared using the negative electrode sheets of Examples 1 to 4 of the present invention have higher first-cycle discharge specific capacity, better cycle performance, lower charge transfer resistance, higher sodium ion diffusion coefficient, and lower metal content in the negative electrode layer after 1000 cycles, indicating that the multifunctional layered multi-metal oxide coating, that is, the negative electrode sheet of the second negative electrode coating comprising a multi-metal oxide, significantly improves the battery performance, and has significantly improved the safety and life.
[0261] In addition, by comparing the analysis of Example 1 with that of Example 2, it can be seen that by making the capacity of the layered multi-metal oxide of the present invention ≥ 100 mAh / g, such as in the range of 100 to 750 mAh / g, and the specific surface area of the layered multi-metal oxide in the range of 100 to 200 m 2 / g, preferably 120~170m 2 / g range, the pore size of the porous structure of the layered multi-metal oxide is 10nm-20nm, preferably in the range of 14nm-16nm, the interlayer spacing of the layered multi-metal oxide is 0.2nm-1.0nm, preferably in the range of 0.3nm-0.8nm, the performance of the prepared negative electrode plates is not much different, all of which have obtained high initial discharge specific capacity and good cycle performance, and the charge transfer resistance is significantly reduced, and the sodium ion diffusion coefficient is significantly increased, indicating that the electrochemical reaction kinetics is significantly improved, which is beneficial to the improvement of the electrical performance of the battery.
[0262] Through the analysis and comparison of Example 1 with Example 3 and Example 4, it can be seen that the performance of the negative electrode sheets prepared by adopting the conditions such as the content and thickness of each substance in the first negative electrode coating and the second negative electrode coating defined in the present invention is not much different, and all of them have obtained a higher initial discharge specific capacity, good cycle performance, improved sodium ion diffusion coefficient, and improved battery electrical performance.
[0263] Parts of the present invention that are not described in detail are well known to those skilled in the art.
[0264] The basic principle of the present invention is described above in conjunction with specific embodiments. However, it should be pointed out that the advantages, strengths, effects, etc. mentioned in the present invention are only examples and not limitations, and it cannot be considered that these advantages, strengths, effects, etc. must be possessed by each embodiment of the present invention. In addition, the specific details disclosed above are only for the purpose of illustration and facilitation of understanding, rather than limitation, and the above details do not limit the present invention to being implemented by adopting the above specific details.
[0265] It should be noted that the term "and / or" or " / " used in this document is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. The singular forms of "a", "the" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0266] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0267] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A negative electrode plate, characterized in that: The negative electrode plate comprises: current collector; A first negative electrode coating is disposed on at least one side of the current collector along the thickness direction, wherein the first negative electrode coating comprises a negative electrode active material; and The second negative electrode coating is disposed on a surface of the first negative electrode coating away from the current collector, wherein the second negative electrode coating comprises a layered multinary metal oxide, wherein the layered multinary metal oxide comprises at least two metal elements, and the layered multinary metal oxide satisfies at least one of the following characteristics: (I) The capacity of the layered multi-metal oxide is ≥ 100 mAh / g; (II) The specific surface area of the layered multi-metal oxide is ≥ 100 m 2 / g; (III) the layered multi-metal oxide has a porous structure; (IV) The interlayer distance of the layered multi-metal oxide is ≥0.15 nm.
2. The negative electrode sheet according to claim 1, characterized in that: The capacity of the layered multi-metal oxide is 100 to 800 mAh / g, preferably 100 to 750 mAh / g; and / or, The specific surface area of the layered multi-metal oxide is 100 to 200 m 2 / g, preferably 120 to 170 m 2 / g; and / or, The pore size of the porous structure is in the range of 10 nm to 20 nm, preferably 14 nm to 16 nm; and / or, The interlayer distance of the layered multi-metal oxide is 0.2 nm to 1.0 nm, preferably 0.3 nm to 0.8 nm.
3. The negative electrode sheet according to claim 1, characterized in that: The chemical formula of the layered multi-metal oxide is M1 2+ x M2 3+ y O z , wherein M1 and M2 are selected from transition metal elements, wherein 0.4≤x≤0.8, 0.2≤y≤0.4, and z=(2x+3y) / 2; Preferably, the M1 includes at least one of Ni, Zn, Mn, Mg, Cu or Co, the M2 includes at least one of Fe, Bi, Al, V or Co, and M1 and M2 are not selected from Co at the same time.
4. The negative electrode sheet according to claim 1, characterized in that: The negative electrode active material includes at least one of graphite, soft carbon or hard carbon; Preferably, the first negative electrode coating further comprises a first binder and a first conductive agent; Preferably, the first binder includes at least one of polyvinylidene fluoride, styrene-butadiene rubber, sodium hydroxymethyl cellulose, polyacrylic acid, polyacrylate, polyvinyl alcohol, polytetrafluoroethylene, polyethylene oxide, carboxypropyl methyl cellulose or hexafluoropropylene; Preferably, the first conductive agent includes at least one of conductive carbon black, conductive graphite, carbon nanotubes, graphene or vapor-grown carbon fiber; Preferably, the mass ratio of the negative electrode active material, the first conductive agent and the first binder is (90-94): (1-6): (2-4).
5. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The second negative electrode coating further includes a second binder and a second conductive agent; Preferably, the second binder includes at least one of polyvinylidene fluoride, styrene-butadiene rubber, sodium hydroxymethyl cellulose, polyacrylic acid, polyacrylate, polyvinyl alcohol, polytetrafluoroethylene, polyethylene oxide, carboxypropyl methyl cellulose or hexafluoropropylene; Preferably, the second conductive agent includes at least one of conductive carbon black, conductive graphite, carbon nanotubes, graphene or vapor-grown carbon fiber; Preferably, the mass ratio of the layered multi-metal oxide, the second conductive agent and the second binder is (90-94): (2-6): (2-4); Preferably, the thickness of the second negative electrode coating is 2 μm to 6 μm; Preferably, the thickness ratio of the second negative electrode coating to the first negative electrode coating is 1:(10-30).
6. The method for preparing a negative electrode sheet according to any one of claims 1 to 5, characterized in that: The following steps are involved: Coating a first negative electrode slurry on at least one side of the current collector to obtain a first negative electrode coating; Coating a second negative electrode slurry on the surface of the first negative electrode coating to obtain a second negative electrode coating; The first negative electrode coating layer includes a negative electrode active material, and the second negative electrode coating layer includes a layered multi-metal oxide.
7. The method for preparing a negative electrode sheet according to claim 6, characterized in that: The preparation of the layered multi-metal oxide comprises: The M1 salt, the M2 salt, water and urea are mixed, and after hydrothermal reaction, washing, drying, calcining and ball milling, a layered multi-metal oxide is obtained; Preferably, the anions of the M1 salt and the M2 salt respectively include at least one of nitrate ion, sulfate ion, chloride ion or acetate ion; Preferably, the M1 element of the M1 salt includes at least one of Ni, Zn, Mn, Mg, Cu or Co, the M2 element of the M2 salt includes at least one of Fe, Bi, Al, V or Co, and M1 and M2 are not selected from Co at the same time; Preferably, the molar ratio of the M1 salt, the M2 salt and the urea is (5-7): (0.5-1.5): 10; Preferably, the temperature of the hydrothermal reaction is 120°C to 180°C, and the time of the hydrothermal reaction is 8h to 12h; Preferably, the calcination temperature is 450°C to 500°C, and the calcination time is 1h to 2h; Preferably, the ball milling speed is 50-70 r / min, and the ball milling time is 12h-24h.
8. The method for preparing a negative electrode sheet according to claim 6 or 7, characterized in that: The preparation of the first negative electrode slurry includes: uniformly mixing the negative electrode active material, the first conductive agent and the first binder in a solvent to obtain the first negative electrode slurry; The preparation of the second negative electrode slurry includes: uniformly mixing the layered multi-metal oxide, the second conductive agent and the second binder in a solvent to obtain the second negative electrode slurry; Preferably, the first negative electrode slurry is coated on the surface of the current collector, and after drying, a first negative electrode coating is formed on the surface of the current collector; the second negative electrode slurry is coated on the first negative electrode coating, and after drying, a second negative electrode coating is formed on the surface of the first negative electrode coating to obtain a negative electrode sheet.
9. A battery comprising a positive electrode sheet and a negative electrode sheet, characterized in that: The negative electrode plate is the negative electrode plate according to any one of claims 1 to 5 or the negative electrode plate made according to the method according to any one of claims 6 to 8.
10. The battery according to claim 9, characterized in that The positive electrode sheet includes a positive electrode coating, the positive electrode coating includes a positive electrode active material, and the positive electrode active material includes a Prussian blue positive electrode material; Preferably, the chemical general formula of the Prussian blue-based cathode material is Na x M3[M4(CN)6] y ·zH2O, where 0 < x ≤ 2, 0.8 ≤ y ≤ 1, 0 < z ≤ 20, and M3 and M4 are respectively selected from transition metal elements; Preferably, the positive electrode coating further comprises a positive electrode conductor and a positive electrode binder, and the mass ratio of the positive electrode active material, the positive electrode conductor and the positive electrode binder is (90-94): (1-6): (2-4).
Citation Information
Patent Citations
Electrode, preparation method thereof, and lithium ion capacitor battery
CN109301160A
Layered bimetallic oxide negative electrode material and preparation method and application thereof
CN114824331A
Negative plate, preparation method of negative plate and battery
CN116825965A
Negative pole piece and electrochemical device
CN117650227A
Active material for battery and manufacturing method therefor
JP2003142097A
Cited By
Positive plate, preparation method thereof and battery
CN121506869A
Positive electrode sheet, method for manufacturing the same, and battery
CN121506869B